Appendicular ‘Googlies’ – Googlies bowled at us by the human vermiform appendix and mimickers of it’s acute inflammation ! – A Case series with Review of literature - M, Vinoth; Joshi, Abhijit; Shetty, Shreya (Eastern Journal of Medical Sciences, 2022)
Objective: Acute appendicitis is one of the common abdominal emergencies encountered in surgical practice. However there are a host of other medical and surgical conditions that closely mimic it, clinically. The objective of this paper is to present a study and analysis of our burden of incidental encounters with such mimicking surgical conditions that were erroneously diagnosed as acute appendicitis, prior to surgery. Methods: Data was retrieved from the hospital’s electronic medical records about all patients operated for acute appendicitis, by a single surgeon, over a 14 year period. Results: A total of 450 patients were operated for acute appendicitis from 2008 to 2022. Out of these, we identified 20 patients who had a normal appendix with some other mimicking surgical condition (Incidence 4.44%). Conclusion: Acute appendicitis has many differential diagnoses, both common and rare. At times, some of these are confirmed ‘on table’; as seen in this case series. A sound, reliable and fool proof palpatory assessment of the abdomen is crucial in diagnosing it’s surgical conditions. It is interesting to note that although the initial diagnosis of acute appendicitis made for all the subjects of this case series was erroneous, all still turned out to have alternate conditions which merited surgery.